ANALYSIS OF TRAINING, COMMUNICATION AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT. ASDP INDONESIA - Muhammad Ridwan; Yohny Anwar; Muhammad Toyib Daulay (RADJA PUBLIKA, 2025)
This study was conducted to examine the extent to which training, communication, and career development affect employee performance with job satisfaction as an intervening variable at PT. ASDP Indonesia Ferry (Persero). Singkil Branch. In the face of increasingly competitive business competition, companies are required to manage human resources effectively to improve the quality of services and organizational performance. Proper training, effective communication, and a structured career development system are believed to be able to increase job satisfaction which ultimately has an impact on improving employee performance. This study uses a quantitative approach with the type of associative research. The research population is all employees totaling 96 people and all of them are sampled through saturated sampling techniques. Data was collected using a questionnaire with a Likert scale and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) through SmartPLS. The results of the study show that training, communication, and career development have a positive and significant effect on job satisfaction. In addition, these three variables and job satisfaction also have a positive and significant effect on employee performance. Job satisfaction has been shown to have the strongest influence on performance and is able to significantly mediate the relationship between training, communication, and career development on employee performance. These findings confirm that job satisfaction plays a strategic role in improving employee performance. Therefore, companies need to strengthen relevant training programs, improve the effectiveness of internal communication, and provide a fair and transparent career development system to drive employee satisfaction and performance on an ongoing basis.